2005
DOI: 10.1128/mcb.25.24.11019-11029.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NDR Protein Kinase by Hydrophobic Motif Phosphorylation Mediated by the Mammalian Ste20-Like Kinase MST3

Abstract: NDR protein kinases are involved in the regulation of cell cycle progression and morphology. NDR1/NDR2 protein kinase is activated by phosphorylation on the activation loop phosphorylation site Ser281/Ser282 and the hydrophobic motif phosphorylation site Thr444/Thr442. Autophosphorylation of NDR is responsible for phosphorylation on Ser281/Ser282, whereas Thr444/Thr442 is targeted by an upstream kinase. Here we show that MST3, a mammalian Ste20-like protein kinase, is able to phosphorylate NDR protein kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(169 citation statements)
references
References 54 publications
6
163
0
Order By: Relevance
“…We also noted that in plate crosses strains carrying the cbk1T3HA allele showed a reduced mating efficiency that was more pronounced in cbk1T3HA 3 cbk1T3HA crosses; in quantitative tests they yielded 40% diploids when crossed to the wild type, compared to 70% in wild-type (wt) 3 wt crosses ( Figure 1). Like other protein kinases in the NDR family, Cbk1p is regulated by phosphorylation (Stegert et al 2005;Hergovich et al 2006), the autophosphorylation of serine 570 in the activation loop, and phosphorylation of threonine 743, in a hydrophobic C-terminal motif ( Jansen et al 2006). In Cbk1T3HAp, the three copies of the HA epitope are inserted close to the serine that is autophosphorylated.…”
Section: Resultsmentioning
confidence: 99%
“…We also noted that in plate crosses strains carrying the cbk1T3HA allele showed a reduced mating efficiency that was more pronounced in cbk1T3HA 3 cbk1T3HA crosses; in quantitative tests they yielded 40% diploids when crossed to the wild type, compared to 70% in wild-type (wt) 3 wt crosses ( Figure 1). Like other protein kinases in the NDR family, Cbk1p is regulated by phosphorylation (Stegert et al 2005;Hergovich et al 2006), the autophosphorylation of serine 570 in the activation loop, and phosphorylation of threonine 743, in a hydrophobic C-terminal motif ( Jansen et al 2006). In Cbk1T3HAp, the three copies of the HA epitope are inserted close to the serine that is autophosphorylated.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that the two fragments remain associated, like cleaved Bid, and that the myristate provides a novel localization site for cleaved MST3 (10). Similar to ctPAK2, MST3 regulates cell morphology but also plays a role in cell cycle progression (37). In addition, overexpression of full-length MST3 or its N-terminal cleavage product is proapoptotic (36).…”
Section: Discussionmentioning
confidence: 99%
“…They further showed that NDR1/2 are essential for the G1/S cell cycle transition by regulating p21 and c-myc levels [76][77][78]. Significantly, NDR1/2 kinases require only MST3 kinase activity for this cell cycle role, but not MST1/2 [76,79]. In contrast, MST1 signalling is indispensable for NDR's regulation of centrosome duplication in S-phase [80,81].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%